BEHAVIORAL ECONOMICS AND ISLAMIC BUSINESS ETHICS: A STUDY OF CONSUMER DECISION-MAKING IN DUBAI’S HALAL ECONOMY - Khaled Al-Mansoori; Aisha Al-Suwaidi; Ahmed Al-Khalil; Françoi Tchoffo (Sharia Oikonomia Law Journal, 2025)
The intersection of behavioral economics and Islamic business ethics offers new insights into consumer behavior within rapidly expanding halal markets. In Dubai, a global hub for Islamic finance and halal commerce, consumer decision-making is influenced not only by economic rationality but also by religious values and ethical frameworks. This study investigates how Islamic ethical principles and cognitive biases interact in shaping consumer choices within Dubai’s halal economy. A mixed-methods approach was employed, combining behavioral experiments with survey data from 412 Muslim consumers across food, fashion, and finance sectors. The study analyzed the effects of ethical priming, religiosity, and framing on purchase intentions, brand loyalty, and risk aversion. Findings indicate that consumers exhibit strong ethical sensitivity, especially when religious cues are salient, and that Islamic ethical commitments often moderate conventional behavioral anomalies such as loss aversion and hyperbolic discounting. The research concludes that behavioral interventions aligned with Islamic ethics can enhance trust, compliance, and long-term loyalty in halal markets. The study contributes to both behavioral economics and Islamic business ethics by integrating moral reasoning with behavioral modeling to better understand decision-making in value-driven economies.